Optimisation of 25-OH D Elisa Kit Usage Using EDTA, Heparin, and Gel Blood Tubes - Sefina, Nadia; Achyar, Afifatul; Wahyuni, Ira (Universitas Ibn Khaldun Bogor, 2025)
The use of anticoagulants in blood collection tubes is also an important factor in the measurement of vitamin D and its metabolites. Vitamin D levels in circulating blood can be measured by measuring 25-hydroxyvitamin D levels in blood. This study aims to compare the effectiveness of using EDTA, heparin, and gel blood tubes in maintaining the stability of 25-OH D in blood samples. The type of research used is Analytical Descriptive research. The samples used in this study used venous blood which was determined using the Simple Random Sampling technique. Samples were taken from 5 semester S1 internship students totalling three people to take blood. Where the blood was taken as much as 3 cc and divided into several purple, green and yellow vacuntainer tubes. From the data obtained, it shows that the use of vacutainer tubes in blood storage to obtain serum for the most optimum vitamin D level test is in a tube with a green lid containing lithium heparin anticoagulant. Where the results obtained on lithium heparin anticoagulant are in the range of >60 ng/mL. As strong evidence of no potential adverse effects at high (optimal) levels. Tubes with purple or lavender coloured covers containing EDTA had results <20 ng/mL indicating that vitamin D deficiency may occur due to lack of vitamin D nutrition. On the other hand, the tube with yellow coloured lid containing anticoagulant gel showed >100 ng/mL indicating vitamin D excess.